Increasing critical thinking skills by using electronic modules based on flipped classroom virus material for phase e students - Radhisa, Fitri Qalbina; Paidi , Paidi; Samsi , Irnayanti Fadhillah (JURNAL BIOEDUKATIKA, 2024)
Students critical thinking abilities can be improved through the use of innovative learning resources in order to achieve these competencies. This research aims to determine the feasibility, practicality and effectiveness of electronic modules based on flipped classroom circulation system material for class XI SMA. Researchers used the R&D development method with the ADDIE development model with stages: Analysis, design, development, implementation and evaluation. The subjects of this research are material experts and media experts. The instrument used in this research was a questionnaire. Data analysis uses a Likert scale. The results of this research show that the product is suitable for use based on the material expert's assessment of 93.58% (very feasible) and the media expert's assessment of 86.9% (very feasible). It is practically used based on the biology teacher's assessment of 95.38% (very practical) and small-scale test results of 91.02% (very practical), and is effective for improving students' critical thinking skills based on the N-gain score with a value of 0.61